(untitled) (Veterinary Science, 2017)
Residues aqueous, methanolic and chloroformic extracts of Centaurea solstüialis L. Compositae flowers, commonly known as Abrepuño, were resuspended with an excipient mixture of Tween 80 (T80) and Carboxymethyl cellulose (CMC) and administered through a gastric catheter to female Wistar rats in order to study the citoprotective properties ofthe plant on ulcers caused by stress due to immersion in water. The essay were carried out by administering T80 + CMC to a group of five rats as control. Other four groups, of equal number of animals, were treated with aqueous (a), methanolic (b), methanolic-chloroformic (1:1) (c) and chloroformic residues,a ll of them resuspendedin a mixture of T80 + CMC. Prevention to ulcers in a, c and d groups was 100%, whereas a 78%o was reached in grou b (p0.05). The methanolic and chloroformic extracts, which contain flavonoid and sesquiterpenela ctonesr espectively, would be responsiblef or the citoprotective effects shown by these results.